Impact of milk fat globule replacement with emulsified canola oil droplets on the composition, structure, texture, sensory properties, and lipid oxidation of fresh soft rennet cheese - M.M. Kasprzak; D. Najgebauer-Lejko; A. Pluta-Kubica; K. Turek; J. Domagała; T.P. Czaja (Journal of Dairy Science)
ABSTRACT: The objective of the study was to improve the nutritional quality of fresh soft rennet cheese by replacing milk fat with canola oil. The structure matrices of soft rennet cheese with 50% and 100% milk fat replacement by canola oil were designed, resulting in an analog 50% and 100%, respectively. Before the formulation, the canola oil was encapsulated by whey protein as a lipid carrier. A control cheese was produced with 3% milk fat with a volume moment mean, D(4,3) of 4.25 µm, whereas the analog 100% was manufactured with 3% canola oil with D(4,3) of 4.62 µm. The analog 50% was fabricated with 1.5% milk fat and 1.5% canola oil, with D(4,3) of 4.87 µm. Analogs and cheese resulted in a lipid content of 17.50% to 18.76%, and droplet size of 1.52 to 2.34 µm. Due to a high concentration of oleic acid (C18:1n-9) in canola oil, the nutritional value, hypocholesterolemic/hypercholesterolemic ratio, and atherogenic and thrombogenic indices of analogs were significantly greater compared with their counterparts of cheese control. The incorporation of canola oil did not compromise in color, lipid oxidation, hardness, adhesiveness, springiness, or cohesiveness in the fresh products. The overall quality of analog 50% was not significantly different to the cheese control, whereas its value reduced in analog 100%. This could be interconnected with the reduction of taste quality when canola oil incorporation increased. The study demonstrated the nutritional and structural potential of emulsion application but some sensory limitations in replacing milk fat lipids.